Letter - Montagu-Pollock, Elizabeth
026-0108-001 National Joint Committee for Spanish Relief Chairman: THE DUCHESS OF ATHOLL. D.B.E., D.C.L. VICE-CHAIRMEN: THE EARL OF LISTOWEL; MISS ELEANOR RATHBONE. M.P. Hon Secretaries: MR. D.R. GRENFELL M.P. LT-COL. J. R. J. MACNAMARA. M.P. MR. WILFRID ROBERTS. M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD. P.C., K.C. Organising Secretary: DR. BETTY MORGAN. ASSISTANT SECRETARY: FELICE CLARK. 4 GREAT SMITH STREET, LONDON, S.W.1 TELEPHONE: ABBEY 2565 2nd May 1939 Mr Bell, T.U.C. Transport House, Smith Street, S.W.1. Dear Sir, I am forwarding herewith 200 Mexican Cards from our own store, and have ordered another 350 from Paris which should arrive within the next day or so when I will send you a further 150. Yours truly, C.E. Montagu-Pollock Secretary, British Committee for Refugees from Spain. EAB 292/946/26/108